The correlation between the use of artificial intelligence and student morality at MTs Labanan Makmur - Reka Oktavia; Rahmad Hakim (ARKA INSTITUTE, 2026)
The rapid integration of Artificial Intelligence (AI) in education raises questions regarding its impact on student morality. This study aims to examine the correlation between AI usage and the moral character of students at MTs Labanan Makmur. Using a quantitative correlational design, data were collected from 35 seventh-grade students selected via purposive sampling. A validated Likert-scale questionnaire was utilized, and the data were analyzed using the Pearson Product-Moment correlation. The results revealed a significant positive relationship between AI usage and student morality (r = 0.3443, p < 0.05). However, the correlation strength is classified as weak, indicating that AI only partially contributes to moral development. The findings emphasize that while AI serves as a constructive cognitive tool, it cannot substitute the irreplaceable human elements essential for character building, such as teachers' role modeling (uswah hasanah) and parental guidance. This study concludes that integrating religious digital literacy is crucial in Islamic educational institutions to ensure that technological competence aligns harmoniously with students' moral maturity.